2015
DOI: 10.1080/15384047.2015.1095412
|View full text |Cite
|
Sign up to set email alerts
|

Development of a radiofrequency ablation platform in a clinically relevant murine model of hepatocellular cancer

Abstract: RFA is used in treatment of patients with hepatocellular cancer (HCC); however, tumor location and size often limit therapeutic efficacy. The absence of a realistic animal model and a radiofrequency ablation (RFA) suitable for small animals presents significant obstacles in developing new strategies. To establish a realistic RFA platform that allows the development of effective RFA-integrated treatment in an orthotopic murine model of HCC, a human cardiac radiofrequency generator was modified for murine use. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…18 21 25 Image-guided RFA offers a reliable and reproducible modality to treat hepatic lesions with minimal collateral damage to the surrounding hepatic parenchyma. 13…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 21 25 Image-guided RFA offers a reliable and reproducible modality to treat hepatic lesions with minimal collateral damage to the surrounding hepatic parenchyma. 13…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib synergizes with RFA to improve anti-HCC immune response in the setting of HCC Sunitinib has the capacity to significantly improve RFA therapeutic efficacy. We have previously demonstrated that RFA resulted in apoptotic tumor death, 13 and that tumor-induced immunotolerance was suppressed by sunitinib. 18 25 Thus, we hypothesized that the improved therapeutic efficacy of the combinatorial treatment was Open access attributed to immune activation.…”
Section: Rfa In Combination With Sunitinib Significantly Improves Antmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of a clinically relevant murine model of HCC was made as described [ 21 , 22 ]. Briefly, potential oncogenic hepatocytes were isolated from young male MTD2 mice.…”
Section: Methodsmentioning
confidence: 99%
“…As our previous performance [ 22 ], liver or tumor biopsies were freshly harvested from normal and tumor-bearing mice and frozen immediately by keeping tissue jar in a beaker of 2-methylbutane in dry ice. The frozen tissues were initially stored at −80°C, and transferred to −20°C on the day before sectioning on a cryostat (MICRON, HM 525, Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%